Tailoring Alginate Nanoparticles: Influence of Reverse Micelle Templates on Structure, Size, and Encapsulation Properties - Duque Lizarazo, Fanny Melina (2025)
In this work, alginate nanoparticles (ALG-NPs) were synthesized using reverse micelles (RMs) as nanoreactors to investigate how interfacial charge influences their structure, size, and encapsulation properties. Three types of RMs were employed: (i) anionic RMs formed by sodium bis(2-ethylhexyl)sulfosuccinate (AOT) in isopropyl myristate, (ii) cationic RMs formed by benzyl-hexadecyl-dimethylammonium chloride (BHDC) in toluene, and (iii) nonionic RMs formed by 2-[4-(2,4,4-trimethylpentan-2-yl)phenoxy]ethanol (TX-100) in cyclohexane. ALG-NPs were synthesized at varying water contents (W0 = [H2O]/[surfactant]) and resuspended in water at pH 6.5 for characterization. Dynamic light scattering revealed that nanoparticle size is highly dependent on the RM template. ALG-NPs synthesized in AOT RMs were the smallest, with their size increasing as W0 increased, a trend also observed for TX-100 RMs. In contrast, the opposite behavior was observed in BHDC RMs, where nanoparticle size decreased with increasing W0. This difference reflects the degree of crosslinking with Ca2+ ions as influenced by interfacial charge. Using N,N-dimethyl-6- propionyl-2-naphthylamine (PRODAN) and curcumin, we found that AOT-based ALG-NPs were the most compact and rigid, offering prolonged protection for curcumin against degradation under ambient conditions. This study underscores the potential of tailoring ALG-NPs through precise control of interfacial environments, offering new opportunities for applications in food technology, nutraceuticals, and biotechnology. By stabilizing bioactive compounds and enhancing bioavailability, these findings pave the way for innovative functional formulations.